A qualitative exploration of the impact of knowledge and perceptions about hypertension in medication adherence in Middle Eastern refugees and migrants - Wejdan Shahin; Gerard A. Kennedy; Ieva Stupans (Elsevier, 2021)
Background: Knowledge and perceptions about chronic disease and medications play a crucial role in determining long-term treatment adherence to diseases such as hypertension. Exploring in depth the barriers and enablers to medication adherence in specific population subgroups such as Middle Eastern refugees and migrants in Australia is important. This may provide a better understanding of each of these groups' beliefs and knowledge and suggest strategies and interventions to improve medication adherence. Objectives: This study aimed to understand Middle Eastern refugees' and migrants' experiences, perceptions, and knowledge about hypertension and to explore factors affecting medication adherence. Methods: In this study 15 participants who identified themselves as Middle Eastern refugees and migrants in Australia and had been diagnosed with hypertension were interviewed (migrants = 5, refugees =10) using semi-structured interviews. Recorded interviews were analysed using a thematic analysis framework and the findings were reported according to consolidated criteria for reporting qualitative research. Results: Three key themes emerged from the interview analysis: (1) dealing with the illness in terms of understanding the symptoms and causes, self-managing of high blood pressure, and coping and acquaintance with the illness; (2) beliefs, practices around medication adherence and the barriers and facilitators to taking medications regularly; and (3) healthcare encounters represented by participants trust in healthcare providers. Differences were found between refugees and migrants relating to the understanding, control, and coping with hypertension, beliefs about medications, trust of healthcare providers, and taking medications as prescribed. There were also differences in the social context of the two groups. Conclusion: Understanding the factors that prevent adherence to hypertension in Middle Eastern refugees addressed the gap in the literature regarding refugees' beliefs and medication adherence. Future studies are recommended to assess the improvement in medication adherence in refugees by modifying their beliefs, attitude, and knowledge about medications and illness. In addition, healthcare providers should consider the differences between Middle Eastern refugees and migrants when providing the health advice that targets each of these population independently to ultimately improve their overall health and adherence to medications.